Syoof Khowman Alwan Determine concentration of Immunoglobulin IgG,IgM,IgA and complement components C 3 and C 4 in serum of women effected with breast cancer - Khowman, Syoof (University of Thi-Qar Journal of Science, 2019)
This study was carried out to investigate some immunological aspects in women effected with breast cancer compared with healthy control groups .The study included (20) patients with breast cancer and (18) healthy women, their age ranged between (21-74) years.The concentration of immunoglobulins (IgG, IgA, IgM) and complement component C3 and C4 were evaluated in twostudied groups . The concentration of immunoglobulins IgG was showed a significant increase pvalue in patientswith breast cancer as compared with control group. No significant differences were observed in respect to the immunoglobulins l evels of IgM and IgA between the studied groups .The concentration of complement component (C 3,C4) were showed a significant increase pvalue in patients with breast cancer as compared with control group (healthy women ).